(untitled) (Ameghiniana, 2014)
The rare archosaurian records from the Triassic Cuyo Basin include that of actosaurs in the Potrerillos Formation. This putative record was based on a pair of poorly preserved, isolated dermal scutes that were tentatively referred to a new species of Typothorax Cope. Examination of this material led to the conclusion that it is not referable to this North American genus; moreover, its attribution to Aetosauria is doubtful.